PENERAPAN METODE COMPOSITE LOGIC UNTUK PERANCANGAN FRAMEWORK PENGUMPULAN BUKTI DIGITAL PADA MEDIA SOSIAL - Al Jumah, Muhammad Naim; Sugiantoro, Bambang; Prayudi, Yudi (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2019)
Social media has become a major part of society. But most of the time social media is used as a way people commit the crime. Due to numerous crimes that use social media, it is essential to design a framework to gather digital evidence on social media. This study develops the design of Framework by implementing Composite Logic Model. A logic Composite model can be used to determine the role model of any variable or pattern that need to collaborate. Composite Logic Model will produce a role model that has a role to produce patterns so that it can produce the same goal. A method of Composite Logic will collaborate with the Digital Forensics Investigation framework to produce a Digital Evidence Collection Framework on Social Media. Based on data and facts, this study has been producing a new framework of gathering digital evidence on social media. The framework has four main stages in the process of collecting digital evidence on social media including pre-process, collection, analysis, and report.